First report of Mansonella sp. and Dipetalonema gracile in the Amazonian city-dwelling threatened primate, Saguinus bicolor - Dias, Cindy Alves; Silva, Túllio Romão Ribeiro da; Gordo, Marcelo; Conga, David Marcial Fernandez; Lima, Natália Aparecida de Souza; Medeiros, Aline Souza de Menezes; Costa, Edson Rodrigues; Luz, Sérgio Luiz Bessa; Costa, Carlos Henrique Aguiar; Vicente, Ana Carolina Paulo; Nascimento, Thaís Pinto; Aguiar-Silva, Francisca Helena; et al. (Frontiers in Tropical Diseases, 2023)
The pied tamarin, or Saguinus bicolor, is a callitrichid that inhabits Amazon Forest fragments encased within the municipalities of Manaus, Rio Preto da Eva, and Itacoatiara and their outskirts. Therefore, this primate lives in great proximity to humans, and is in critical danger of extinction, resulting from ongoing anthropogenic pressures, with habitat fragmentation being the most prominent threat. Greater conservation efforts and more studies concerning public health need to be carried out in this situation, such as the study of infectious diseases that can affect this primate, including those involving helminths. In this study, we combined necropsy, microscopy with blood smears and quick Panoptic stains, and molecular methods like nested polymerase chain reaction (PCR) targeting the internal transcribed spacer-1 (ITS-1) region, Sanger sequencing and shotgun sequencing to detect and identify filarial parasites in 71 S. bicolor samples. We detected 24 adult filarial worms in 6.45% of the thoracic cavities, microfilaria in 6.38% from blood smears, and filarial DNA in 28.57% positive blood samples via PCR. We identified eight of the adult worms as being from the Onchocercidae family using Sanger sequencing and one specifically as Dipetalonema gracile, using shotgun sequencing. For the positive blood samples, 70.58% of them were for Mansonella sp., 17.64% for Dipetalonema sp., and 11.76% could only be identified as belonging to the Onchocercidae family. There was an event of coinfection that involved Dipetalonema sp. adult worm and Mansonella sp. microfilaria. This is the first report of the detection of Dipetalonema gracile and the genus Mansonella in S. bicolor, as well as an event of coinfection, pointing out this primate as a new host. It is also another step to understand the situation of filarial infections occurring in Amazonian Regions and its municipalities.